2001
DOI: 10.1126/science.1064413
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Histone Lysine Methylation and Developmental Changes at the Chicken β-Globin Locus

Abstract: Methylation of histones at specific residues plays an important role in transcriptional regulation. Chromatin immunoprecipitation of dimethylated lysine 9 on histone H3 across 53 kilobases of the chicken beta-globin locus during erythropoiesis shows an almost complete anticorrelation between regions of elevated lysine 9 methylation and acetylation. Lysine 9 is methylated most over constitutive condensed chromatin and developmentally inactive globin genes. In contrast, lysine 4 methylation of histone H3 correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
424
6
9

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(465 citation statements)
references
References 19 publications
26
424
6
9
Order By: Relevance
“…18 One can also attribute the cell type selectivity to the physiological role of insulators, that is, the regulation of stage-specific gene expression by regulating higher chromatin structure. 16,17 Recently, double-stranded DNA-binding protein, SATB1, was reported to play a key role in forming thymocytespecific nuclear architecture. 34 SATB1 is proposed to be involved in the chromatin loop formation and regulation of histone modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 One can also attribute the cell type selectivity to the physiological role of insulators, that is, the regulation of stage-specific gene expression by regulating higher chromatin structure. 16,17 Recently, double-stranded DNA-binding protein, SATB1, was reported to play a key role in forming thymocytespecific nuclear architecture. 34 SATB1 is proposed to be involved in the chromatin loop formation and regulation of histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, insulators have been shown to exert their activity through the regulation of the chromatin structure. 3,16,17 Therefore, we focused on the epigenetic changes of the integrated vector sequence to unravel the mechanism of action of ArsI. We analyzed the acetylation status of histone H3 in the provirus, which reflects the open state of chromatin fiber as well as DNA methylation.…”
Section: Sea Urchin Insulator In Lentiviral Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperacetylation of histone H3 and H4 lysine residues is generally associated with active chromatin, whereas deacetylation has been correlated with inactive genes (35). Another histone modification that has been associated with transcriptionally active chromatin is methylation at Lys 4 of histone H3 (36,37). In cancer cells, histone modifications work in concert with DNA methylation to silence tumor suppressor genes (13,28,38).…”
Section: Discussionmentioning
confidence: 99%
“…Rb appears to circumscribe heterochromatin in the photoreceptors 14 , whereas it appears in a diffuse nuclear pattern in neurons and progenitor cells. It has been suggested that the genome is divided into transcriptional domains and that this organization is regulated by a higher order chromatin structure that is organized by histones [29][30][31][32] . Rb is recruited to specific promoters through protein-protein interactions with E2F/DP heterodimers bound to their cognate binding sites 33 .…”
Section: Thus Rb Family Members May Not Be Completely Interchangeablmentioning
confidence: 99%